2017
DOI: 10.1039/c7sm00405b
|View full text |Cite
|
Sign up to set email alerts
|

Transport of underdamped active particles in ratchet potentials

Abstract: We study the rectified transport of underdamped active noninteracting particles in an asymmetric periodic potential. It is found that the ratchet effect of active noninteracting particles occurs in a single direction (along the easy direction of the substrate asymmetry) in the overdamped limit. However, when the inertia is considered, it is possible to observe reversals of the ratchet effect, where the motion is along the hard direction of the substrate asymmetry. By changing the friction coefficient or the se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The understanding of these aspects requires a description taking into account the acceleration of the particles, in contrast with the one commonly employed to describe self-propelled systems. As recent studies have shown, inertia affects many properties of active particles, such as their pressure [13][14][15][16][17], transport properties [18,19], the stochastic energetics [20] and, even, anomalous responses to boundary driving [21]. Besides, inertial forces play an important role also at the collective level: i) affecting the clustering typical of active matter and, in particular, suppressing the phase-coexistence [22][23][24][25][26] and changing several features of the transition [27] ii) modifying some properties of dense phases of active matter [28], such as the active temperature in the homogeneous [29] and inhomogeneous phases [30].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of these aspects requires a description taking into account the acceleration of the particles, in contrast with the one commonly employed to describe self-propelled systems. As recent studies have shown, inertia affects many properties of active particles, such as their pressure [13][14][15][16][17], transport properties [18,19], the stochastic energetics [20] and, even, anomalous responses to boundary driving [21]. Besides, inertial forces play an important role also at the collective level: i) affecting the clustering typical of active matter and, in particular, suppressing the phase-coexistence [22][23][24][25][26] and changing several features of the transition [27] ii) modifying some properties of dense phases of active matter [28], such as the active temperature in the homogeneous [29] and inhomogeneous phases [30].…”
Section: Introductionmentioning
confidence: 99%
“…We expect that this approach will be particularly useful in two contexts. Firstly, it will allow the study of systems that are not over-damped; as illustrated in Section V A, such systems can show substantially different behaviour from their over-damped counterparts 21 .…”
Section: Discussionmentioning
confidence: 99%
“…We now present the integrator itself. In each time step of size h, we perform half a step of the Verlet-type integrator for Hamiltonian dynamics, 20 followed by a full time step of the Ornstein-Uhlenbeck process in (21), and finally a second half step of the Verlet-type integrator. Starting from the initial conditions P 0 = p, R 0 = r, Q 0 = q, |q i | = 1, i = 1, .…”
Section: Numerical Integratormentioning
confidence: 99%
See 2 more Smart Citations